Phytoremediation potential of an aquatic weed, Eichornia crassipes, in crude oil contaminated sites - O. Omokeyeke; F.D. Sikoki; E.O. Nwachukwu (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The potential of plant-assisted bioremediation in crude oil polluted aquatic ecosystems was studied. The aim was to access the efficacy of Eichornia. crassipes (Water hyacinth) and their associated microorganisms in the treatment of crude oil contaminated waters and the duration of treatment required for the restoration of acceptable water quality. The experimental approach involved the exposure of the plants to varying concentrations of crude oil (500mg/l, 2500mg/l and 5000mg/l) under laboratory conditionsfor six weeks. From the results, percentage reductions of total hydrocarbon content were 98.46, 99.65 and 99.82% under 500mg/l, 2500mg/l and 5000mg/l of crude oil exposure concentrations respectively. In addition, the total heterotrophic bacteriaand fungi, and the hydrocarbon degrading bacteria and fungi in the exposure media increased from 0.07 to 1.48 Cfu/ml, while the growth of E. crassipes was enhanced from 1kg to 4kg. Water quality variables were also observed to improve significantly with percentage reductions of 99.82, 99.95, 99.99 and 85.05 for chemical oxygen demand, nitrate, phosphate and total organic carbon after six weeks of treatment with E. crassipes. It is concluded that the introduction of E. crassipesin oil contaminated waters resulted intheremoval of the crude oil and restoration of water quality through the interaction of E.crassipes and their associated microorganisms. Thus, E.crassipes can serve as an agent of bioremediation in crude oil contaminated waters